Impact of Negative Discrete Emotion on Subjective Career Success with Mediation Role of Proactive Career Behavior (Journal of Social Sciences Review, 2023)
This study aims to investigate how (ANG) affects the (SCS), using the framework of affective event theory. Furthermore, the study seeks to shed light on the specific ways in which different aspects of (ANG) impact "(SCS)".by exploring the potential mediating role of (PCB). The study's primary objective is to provide light on how people might lessen (ANG's) deleterious effects on their (SCS) by investigating these pathways. Data from 415 individuals with jobs in the service industry in Pakistan was used to conduct statistical tests using a method called "structural equation modelling" (SEM). The study's results show that (ANG) significantly affects many facets of (SCS). Specifically, the findings show a negative direct effect of ANG on SCS, while also revealing a positive association between ANG & (PCB). Moreover, the research shows that PCB mediates the connection between ANG and SCS. Future studies should investigate the function of negative emotions and PCB, and SEFF as mediators of the SCS to fully comprehend its significance for both workers and employers. This problem may be alleviated and biases avoided by using an externally derived scale for a number of constructs.
Keywords: Experience anger (ANG); Subjective Career Success (SCS); Affective Event Theory; Proactive career behavior (PCB)